Optimalisasi Media Pembelajaran Berbasis Website: Wordwall.net untuk Kemudahan Interaksi dan Evaluasi Hasil Pembelajaran Siswa - Tri Sagirani; Nunuk Wahyuningtyas; Sri Hariani Eko Wulandari; Oktaviani (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
The implementation of the Merdeka Curriculum requires teachers to be more creative in preparing learning media. Optimization of website-based media in learning is a necessity. This community service program is carried out to answer challenges for teachers and is carried out in the form of intensive training. The target of the implementation of the activity is teachers at the kindergarten, elementary and special school education levels in East Java. In its implementation, a survey of teachers has been carried out and it was found that teachers need other auxiliary applications to build learning media that students like and are more interesting, and the selected application is wordwall. The Wordwall application is website-based and makes it easier for teachers to evaluate student learning outcomes. From a survey of 213 teachers, 60 teachers were selected to take part in intensive training on the use of wordwall applications. The success of this program is measured by the assessment of participants, that the implementation of the program is going well, in accordance with expectations and providing added value for teachers in developing learning media, this can be seen in the average score given by participants of 3.77 on a scale of 1 to 4.